Ozone Pollution Extremes in Southeast China Exacerbated by Reduced Uptake by Vegetation During Hot Droughts - Meiyun Lin; Yuanyu Xie; Isabelle DeSmedt; Larry W. Horowitz (Geophysical Research Letters)
Abstract Using a decade of observations and chemistry‐climate model simulations (2014–2023), we highlight the key role of biosphere‐atmosphere interactions in driving late summer–autumn ozone pollution extremes over Southeast China during hot droughts. In the 2019 and 2022 droughts, stomatal closure in the Yangtze River Basin, caused by soil moisture deficits, led to ∼60% reductions in ozone deposition rates to vegetation, aligning with reduced photosynthesis inferred from satellite remote sensing of solar induced fluorescence. Ozone production increased due to higher isoprene emissions from heat stress, NOx‐rich airflow from North China, and enhanced solar radiation. Soil drought intensified temperatures and increased isoprene emissions by 27%, but these only had marginal impact on ozone (<5 ppbv) in South China, where ozone formation is NOx‐limited. Reduced ozone uptake by drought‐stressed vegetation played a dominant role, driving 10–20 ppbv increases in daily maximum 8‐hr average ozone concentrations and a threefold rise in events exceeding 100 ppbv.